คุณสมบัติทางเคมีและชีวภาพของสารสกัด lignin และประสิทธิภาพทางพลังงานของกากอ้อยที่เหลือหลังจากการสกัดแยก lignin ด้วยกรดและด่าง: Chemical and Biological Characteristics of Lignin and Energy Efficiency of Acid and Alkali Delignified Bagasse - Boonruangrod, Chutima; Liengprayoon, Siriluck; Morakul, Sumallika (Asian Health, Science and Technology Reports, 2016)
ผลผลิตพลอยได้หลักจากอุตสาหกรรมน้ำตาลได้แก่ กากอ้อย ซึ่งมีปริมาณมหาศาลในแต่ละปีและถูกนำมาใช้ประโยชน์หลักในการผลิตเชื้อเพลิงหมุนเวียนในกระบวนการผลิตน้ำตาล งานวิจัยนี้มีวัตถุประสงค์เพื่อสกัด lignin จากกากอ้อยด้วยกรดและด่าง จากนั้นศึกษาคุณสมบัติของสารสกัดที่ได้และประสิทธิภาพทางพลังงานของกากอ้อยที่เหลือเพื่อเป็นแนวทางในการนำไปใช้ประโยชน์และเพิ่มมูลค่าให้กับผลผลิตพลอยได้จากอุตสาหกรรมน้ำตาล เนื่องจาก lignin นับเป็น polymer ที่มีปริมาณมากเป็นอันดับสองรองจาก cellulose และมีโครงสร้างทางเคมีที่มีศักยภาพในการนำมาใช้ประโยชน์ที่หลากหลาย จากการศึกษาผลได้การสกัดรวมถึงคุณสมบัติของ lignin จากกากอ้อยที่อายุต่างกัน โครงสร้างทางเคมี (FTIR) และคุณสมบัติทางชีวภาพ (antioxidant activity, antimicrobial activity) พบว่าผลได้การสกัดแตกต่างกันไปตามสภาวะการสกัด (1%NaOH และ formic acid: acetic acid: H2O, 30:55:15, v/v/v) สัดส่วนของ solid: liquid ratio (1:6 และ 1:12) อายุของกากอ้อย (หลังหีบ 1 วัน, 10-12 เดือน) รวมถึงการ pretreatment (±steam explosion) โดยกากอ้อยเก่าสามารถสกัด lignin ได้โดยไม่ผ่านการระเบิดด้วยไอน้ำและให้ผลได้สูงสุดเท่ากับ 26% ในขณะที่กากอ้อยใหม่จำเป็นต้องนำมาผ่านการระเบิดด้วยไอน้ำโดยได้ผลได้สูงสุด 22% ตัวทำละลายที่ให้ผลดีที่สุดคือ 1%NaOH อัตราส่วน 1:12 อย่างไรก็ตาม lignin จากกากอ้อยเก่ามีคุณสมบัติในการต้านอนุมูลอิสระต่ำกว่าในกากอ้อยใหม่เล็กน้อยซึ่งอาจเนื่องมาจากการเกิด oxidation ของ lignin บางส่วนในสภาวะการเก็บรักษากากอ้อยภายนอกอาคารของโรงงาน นอกจากนี้ยังพบว่าสารสกัด lignin ที่ความเข้มข้นต่ำสุดที่ 1250 µg/ml (MIC) สามารถยับยั้งการเจริญของเชื้อแบคทีเรียแกรมลบ (E. coli, S. typhimurium & V. cholera) ได้ดีกว่าแกรมบวก (S. aureus) นอกจากนี้กากอ้อยที่ผ่านการสกัดแล้วสามารถนำกลับมาใช้ผลิตไฟฟ้าต่อได้ โดยให้ค่าพลังงานความร้อนลดลงประมาณ 5-19% เมื่อเทียบกับกากอ้อยที่ยังไม่ผ่านการสกัด Large amount of sugar industrial by products mainly bagasse is generated annually and mostly used to produce energy for sugar industry itself. The present work aims at extracting lignin from bagasse using acid and alkali delignification methods. The obtained lignin was characterized for its chemical and biological characteristics including the energy efficiency of delignified bagasse. Indeed, lignin becomes more attractive due to its second largest amount compared to cellulose. Moreover, its chemical structures indicate high potential to be developed for various applications. From extraction process, yield of extracted lignin was varied according to extracting media (1%NaOH and formic acid: acetic acid: H2O, 30:55:15, v/v/v), solid: liquid ratio (1:6 and 1:12), state of obtained bagasse (1 day and 12 day after juice extraction) and pretreatment process (steam explosion). Extraction of twelve month stored bagasse under alkali condition without pretreatment provided the highest yield of 22%. Meanwhile, pretreatment for new bagasse seems necessary in order to improve extraction efficiency when using 1%NaOH at 1:12 ratio. In addition, lignin obtained from twelve month bagasse provided poorer antioxidant activity assessed by DPPH compared to that from new bagasse. This could be due to partial oxidation of lignin under outdoor storage condition of bagasse. Concerning antimicrobial activity, all lignin obtained from all extraction conditions at the concentration of 1,250 µg/ml (Minimum Inhibitory Concentration; MIC) could inhibit microbial growth. The better inhibition was observed in gram negative bacteria (E. coli, S. typhimurium and V. cholera) than gram positive bacteria (S. aureus). In addition, delignified bagasse could be reutilized as an energy source with slight reduction of heat building capacity around 5 - 19% compared to normal bagasse.